Impact of Antibiotic Use during Hospitalization on the Development of Gastrointestinal Colonization with Escherichia coli with Reduced Fluoroquinolone Susceptibility - Han, Jennifer H. (2013)
OBJECTIVE: Infections due to fluoroquinolone-resistant Escherichia coli (FQREC) are associated with significant morbidity and mortality. Fluoroquinolone resistance likely arises at the level of gastrointestinal colonization. The objective of this study was to identify risk factors for the development of FQREC gastrointestinal tract colonization in hospitalized patients, including the impact of antibiotics prescribed during hospitalization. DESIGN: A prospective cohort study was conducted from 2002 to 2004 within a university health system. METHODS: Hospitalized patients initially colonized with fluoroquinolone-susceptible E. coli were followed up with serial fecal sampling for new FQREC colonization or until hospital discharge or death. A Cox proportional hazards regression model was developed to identify risk factors for new FQREC colonization, with antibiotic exposure modeled as time-varying covariates. RESULTS: Of 395 subjects, 73 (18.5%) became newly colonized with FQREC. Length of stay before sampling (hazard ratio [HR], 1.02 [95% confidence interval (CI), 1.1–1.03]; P = .003) and malignancy (HR, 0.37 [95% CI, 0.21–0.67]; P = .001) were significantly associated with the development of FQREC colonization. In addition, receipt of a first-generation cephalosporin (HR, 1.19 [95% CI, 1.10–1.29]; P < .001) or cefepime (HR, 1.05 [95% CI, 1.00–1.10]; P = .048) during hospitalization increased the risk of new FQREC colonization. CONCLUSIONS: The acquisition of FQREC in the hospital setting is complex, and antimicrobial stewardship programs should take into account patterns of antibiotic use in implementing strategies to reduce the development of new FQREC colonization. Future studies are needed to identify risk factors for infection in hospitalized patients newly colonized with FQREC.